Platform Digital Dalam Penyelenggaraan Pelayanan Publik Di Kelurahan Malalayang Satu Barat Kecamatan Malalayang Kota Manado: Digital Platform in the Implementation of Public Services in Malalayang Satu Barat Urban Village, Malalayang Sub-district Manado City (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
The digital platform referred to in this PKM is whatsapp (WA) in the context of public services in Malalayang Satu Barat urban village. The target partners are located in Malalayang Satu Barat Urban Village, Manado City. The problem is many people in neighbourhood III of Malalayang Satu Barat village who lack knowledge and use of technological information for the use of digital platforms or whatsapp (WA) that has been created by the head of neighbourhood III, there are people using the WA group by buying and selling groceries and food instead of how to use this digital platform as a medium for exchanging information between the government and the community in order to improve services to the community. The specific target is to produce community understanding by using the existing WA group, it is hoped that the entire community of neighbourhood III can be presented with various services or information in order to create excellent public services. The implementation methods to this programme are the agreed partner problem is the use of a digital platform (WA); the approach methods that will be offered to overcome partner problems are counseling, socialisation, and mentoring;  The work mechanism includes surveys, counseling, socialisation, outcomes, reporting. The benefit of this activity is to increase social capital.